A Nanozyme‐Immobilized Hydrogel with Endogenous ROS‐Scavenging and Oxygen Generation Abilities for Significantly Promoting Oxidative Diabetic Wound Healing. Issue 22 (9th October 2022) - Li, Zuhao; Zhao, Yue; Huang, Hanwei; Zhang, Changru; Liu, He; Wang, Zhonghan; Yi, Mingjie; Xie, Neng; Shen, Yuling; Ren, Xiangzhong; Wang, Jincheng; Wang, Jinwu
Abstract: Non‐healing wound is a common complication of diabetic patients associated with high morbidity and mortality. Engineered therapeutic hydrogels have enviable advantages in tissue regeneration, however, they are suboptimal for the healing of diabetic wounds characterized by reactive oxygen species (ROS) accumulation and chronic hypoxia. Here, a unique biological metabolism‐inspired hydrogel, for ameliorating this hostile diabetic microenvironment, is presented. Consisting of natural polymers (hydrazide modified hyaluronic acid and aldehyde modified hyaluronic acid) and a metal–organic frameworks derived catalase‐mimic nanozyme ( ε ‐polylysine coated mesoporous manganese cobalt oxide), the engineered nanozyme‐reinforced hydrogels can not only capture the endogenous elevated ROS in diabetic wounds, but also synergistically produce oxygen through the ROS‐driven oxygen production ability. These fascinating properties of hydrogels protect skin cells (e.g., keratinocytes, fibroblasts, and vascular endothelial cells) from ROS and hypoxia‐mediated death and proliferation inhibition. Diabetic wounds treated with the nanozyme‐reinforced hydrogels highlight the potential of inducing the macrophages polarization from pro‐inflammatory phenotype (M1) to anti‐inflammatory subtype (M2). The hydrogel dressings demonstrate a prominently accelerated healing rate as shown by alleviating the excessive inflammatory, inducing efficiently proliferation, re‐epithelialization, collagen deposition, and neovascularization. This work provides an effective strategy based on nanozyme‐reinforced hydrogel as a ROS‐driven oxygenerator for enhancing diabetic wound healing. Abstract : A nanozyme‐reinforced self‐protecting hydrogel is proposed as an active oxygen species‐driven oxygenerator, which can facilitate skin cells' survival and proliferation in oxidative stress and hypoxia microenvironment. When the hydrogel is engineered as a wound dressing, the satisfactory healing of skin in diabetic rats can be achieved by efficiently promoting macrophages polarization, alleviating inflammation, augmenting cell proliferation, inducing re‐epithelialization, collagen deposition, and angiogenesis.